Nurse Anesthesia - Nagelhout John J (Elsevier Saunders, 2005)
Introduction and Overview, Nurse Anesthesia: A History of Challenge, Specialty Practice of Nurse Anesthesia, Nurse Anesthesia Research: Sciense of an Orderly and Purposeful and Systematic Nature, Scientific Foundations, Pharmacokinetics, Inhalation Anesthetics, Local Anesthetics, Cardiac Pharmacology, Chemistry and Physics, Technology Related to Anesthesia Practice, Anesthesia Equipment, Preoperative Preparation, Clinical Monitoring in Anesthesia, Preoperative Evaluation and Preparations of the Patient, Intraoperative Management, Positioning for Anesthesia and Surgery, Cardiac Anesthesia, Vascular Surgery, The Endocrine System, Trauma Anesthesia, Anesthesia and Lase Surgery, Regional Anesthesia, Pediatric Anesthesia, Pain Management, Anesthesia for Therapeutic and Diagnostic Procedures.